(untitled) (Revista Internacional de Folkcomunicação, 2019)
The aim of this paper is to present hip hop rappers as leaders-communicators that are esencial for the transformation of marginalized urban territories. To do so, it uses as main pillars the theories of Folkcommunication and Cultural Studies, with the exploratory research as methodology. The reflections presented allows to think about the role of rappers as agents of popular communication that produce cultural identities, and also promote discourses that aims to argue against media texts that promote proscribed identities. Through this paper, we purpose to present how the theories of Luiz Beltrão are fundamental for the researches about contemporary popular cultures. Folkcommunication; Cultural identity; Rap.